Strategic Leadership and Entrepreneurial Capability for Game Change. (November 2013) - Abdelgawad, Sondos G.; Zahra, Shaker A.; Svejenova, Silviya; Sapienza, Harry J.
In this article, we introduce the concept of entrepreneurial capability (EC) to capture a firm's capacity to sense, select, and shape opportunities, and synchronize their strategic moves and resources in pursuit of these opportunities. We define EC and explain its dimensions, highlighting its role in achieving and sustaining a firm's competitive advantage. We also propose that EC is instrumental for realizing a firm's game-changing strategies, that is, those strategic moves that fundamentally alter the nature, domain and dynamics of competition. Furthermore, we propose that strategic leadership plays an essential role in honing a company's EC and aligning it with its game-changing strategy by creating an organizational context where transforming the business ecosystem becomes feasible. Finally, we articulate the implications of EC for managerial practices and for advancing future research at the intersection of entrepreneurship, leadership, and competitive strategy.